Enkele strategieë vir ekonomie se ontwikkeling in die informele sektor - Bruyn, H. E. C. de (Koers, 1991)
Since 2 February 1990 the pace of change in South Africa has been accelerating on all fronts. One naturally thinks of political development,but this change applies equally to economic development in the black informal sector There is a need for national and local authorities as well as fo r the private sector to play a role in promoting informal business activities. Instead of legislating away the so-called problem, the reality of the economic situation in the informal sector should be recognised and managed in a supportive manner In a changing society high priority should be given to the nurturing of economic growth in the informal sector. The increasing numbers of the unemployed in South Africa, especially in urban areas, necessitates positive steps to deal with the realities of urbanisation and to ease the way in which honest income can be earned through various opportunities in the informal sector A healthy and growing small business in the informal sector is a vital ingredient to ensure widespread employment and income-creation in a market-orientated economy. This sector of the economy tends to be labour-intensive, is competitive by nature and is noted for the ease of entry - thus being a prime training gun d for entrepreneurship. It is absolutely clear that the growing debate surrounding the informal sector in South Africa should be coupled with the application of reformist development strategies throughout the sub-continent. It order to improve the current situation, some specific strategies to achieve social and economic upliftment in the informal part of the economy are identified by the author. Although the informal sector forms an integral part of the economy as a whole, the focal point of this article is the economic role and function of the black population in the informal sector.